8 Catatonia: demographic, clinical and laboratory associations in a large dataset. Issue 8 (20th July 2020) - Rogers, Jonathan P; Pollak, Thomas A; Begum, Nazifa; Griffin, Anna; Carter, Ben; Pritchard, Megan; Broadbent, Matthew; Kolliakou, Anna; Stewart, Robert; Patel, Rashmi; Bomford, Adrian; Amad, Ali; et al.
Abstract : Objectives/Aims: Catatonia is an important neuropsychiatric disorder with a high morbidity and mortality. However, due to a perception that it is very infrequent and because of the acuity of the patients, it has remained poorly studied and research has often been confined to small groups. We hypothesised that: catatonia would remain a significant clinical problem; catatonic patients would have a longer duration of admission and higher mortality; serum iron would be reduced, reflecting a systemic inflammatory response, and high rates of NMDA receptor antibody serum positivity would be observed. Methods: This was a prospective cohort study that included patients in a large mental health trust who were diagnosed with catatonia between 2007 and 2016. We used the Clinical Records Interactive Search (CRIS) system hosted at the NIHR Maudsley Biomedical Research Centre to search the clinical records for patients with catatonia. An initial free-text search was refined by use of a natural language processing app. The results of the app were validated by three of the authors, who included patients in the analysis only if a clinician had made a diagnosis of catatonia and two or more items of the Bush-Francis Catatonia Screening Instrument were in evidence. Demographic, clinical and blood-based markers could then be extracted for these patients and compared, where relevant, to non-catatonic psychiatric patients. Results: 1, 456 patients with catatonia (of whom 787 were psychiatric inpatients) and 37, 456 psychiatric inpatient controls were identified. There was no evidence for a reduction in the rate of catatonia over time. Patients with catatonia were younger than the controls by 2.52 years (95% CI 1.30 to 3.73) and similar in gender composition. Patients with catatonia were more likely to be black (53.5% vs 24.5%, p<0.001). Duration of hospitalisation was greater in the catatonic group (221 days vs 86 days, p<0.001), but there was no difference in mortality when controlling for demographic variables (HR 0.96 [95% CI 0.84–1.23]). Serum iron was lower in catatonic patients (11.6 vs 14.2 µmol/L [95% CI -4.88 to -0.30 µmol/L]), but there was no difference in C-reactive protein, erythrocyte sedimentation rate or white cell count. NMDA receptor antibodies were present at a higher rate (OR 5.6 [95% CI 1.3–24.1]). Principal component analysis divided the elements of the Bush-Francis Catatonia Screening Instrument into three components (hyperkinetic, hypokinetic and amotivation). Conclusions: This is the largest study of catatonia to date. There is evidence that catatonia is not dying out and confers high morbidity but without affecting mortality. The innate immune system does not seem to be activated, but NMDA receptor antibodies are present at higher rates than in psychiatric controls. We demonstrate that catatonia remains an important clinical problem and may be associated with neuroimmunological dysfunction.